Targeted inhibition of β-catenin alleviates airway inflammation and remodeling in asthma via modulating the profibrotic and anti-inflammatory actions of transforming growth factor-β1. (February 2021) - Huo, Rujie; Tian, Xinli; Chang, Qin; Liu, Dai; Wang, Chen; Bai, Jingcui; Wang, Runjuan; Zheng, Guoping; Tian, Xinrui
Background: TGF-β1 is a key cytokine involved in both airway inflammation and airway remodeling in asthma because of its anti-inflammatory and profibrotic effect. In our previous study, we found that knockdown of cytosolic β-catenin alleviated the profibrogenic effect of TGF-β1 without influencing its anti-inflammatory effect. However, the exact role of targeting β-catenin in asthma is not yet fully demonstrated. In the present study, we investigated the effect and mechanism of targeting β-catenin in OVA-challenged asthmatic rats with airway inflammation and remodeling features. Methods: We integrated experimental asthma model and asthma related cell model to explore the effect of targeting β-catenin on airway inflammation and remodeling of asthma. Results: Blocking β-catenin with ICG001, a small molecule inhibitor of β-catenin/TCF via binding to cAMP-response elementbinding protein, attenuated airway inflammation by increasing levels of anti-inflammation cytokines IL-10, IL-35 and decreasing levels of T helper (Th)2 cells and Th17 cytokine. Suppressing β-catenin by ICG001 inhibited airway remodeling via reducing the level of TGF-β1 and the expressions of Snail, MMP-7, MMP-9 and, up-regulating expression of E-cadherin, down-regulating expressions of α-SMA and Fn. Inhibition of β-catenin with ICG001 suppressed TGF-β1 induced proliferation and activation of CCC-REPF-1, blocked TGF-β1 induced epithelial–mesenchymal transition (EMT) of RLE-6TN. Conclusion: Blockade of β-catenin/TCF not only prevents TGF-β1 induced EMT and profibrogenic effects involved in pathological remodeling of airway, but also alleviates airway inflammation in asthma by balancing pro-inflammatory and anti-inflammatory cytokine. In conclusion, targeting β-catenin specifically via inhibition of β-catenin/TCF might be a new therapeutic strategy for asthma. The reviews of this paper are available via the supplemental material section.